Impact of age on early outcomes and long-term survival of patients undergoing aortic repair with Stanford A dissection. (November 2018) - Merkle, Julia; Sabashnikov, Anton; Weber, Carolyn; Schlachtenberger, Georg; Maier, Johanna; Spieker, Anna; Eghbalzadeh, Kaveh; Deppe, Antje-Christin; Zeriouh, Mohamed; Rahmanian, Parwis B.; Madershahian, Navid; Rustenbach, Christian; et al.
Objectives: Stanford A acute aortic dissection (AAD) is a life-threatening emergency, typically occurring in older patients and requiring immediate surgical repair. The aim of this study was to evaluate early outcome and short- and long-term survival of patients under and above 65 years of age. Methods: Two hundred and forty patients with Stanford A AAD underwent aortic surgical repair from January 2006 to April 2015 in our center. After statistical analysis and logistic regression analysis, Kaplan-Meier survival estimation was performed, with up to 9-year follow-up, comprising patients under and above 65 years of age. Results: The proportion of patients above 65 years of age suffering from Stanford A AAD was 50% (n=120). The group of patients above 65 years of age compared to the group under 65 years of age showed statistically significant differences in terms of higher odds ratios (OR) for hypertension (p=0.012), peripheral vascular disease (p=0.026) and tachyarrhythmia absoluta (p=0.004). Patients over 65 years of age also showed significantly poorer short- and long-term survival. Our subgroup analysis revealed that male patients (Breslow p=0.001, Log-Rank p=0.001) and patients suffering with hypertension (Breslow p=0.003, Log-Rank p=0.001) were reasonable for these results whereas younger and older female patients showed similar short- and long-term outcome (Breslow p=0.926, Log-Rank p=0.724). After stratifying all patients into 4 age groups (<45; 55-65; 65-75; >75years), short-term survival of the patients appeared to be significantly poorer with increasing age (Breslow p=0.026, Log-Rank p=0.008) whereas long-term survival of patients free from cerebrovascular events (Breslow p=0.0494, Log-Rank p=0.489) remained similar. Conclusions: All patients referred to our hospital for repair of Stanford A AAD with higher age had poorer short- and long-term survival, caused by male patients and patients suffering from hypertension, whereas survival of women and survival free from cerebrovascular events of the entire patient cohort was similar, irrespective of age.